Closing special education bachelor's programs in the Kingdom of Saudi Arabia: an analytical perspective and solutions - Saffar, Ohud Adnan (Frontiers in Education, 2025)
The Kingdom of Saudi Arabia's (KSA) closure of special education bachelor's programs (SEBP) has sparked controversy among specialists, but researchers have not yet discussed the reasons and alternative solutions. Therefore, the study examines the opinions of faculty members in KSA universities in special education on this decision in terms of its impact on the quality of education for people with disabilities (PWD) and explores alternative solutions for developing higher education policies. The study also aims to compare special education programs in KSA with those in international universities. The study used a mixed method to analyze the opinions of 20 faculty members from 4 universities in the KSA regarding the decision to close the SEBP, using interviews. The study also analyzed data from 20 websites of top international universities, comparing the results with the SEBP in Saudi universities. It then statistically analyzed the data using an exploratory sequential design. One of the most important results of the study is that 65% of the faculty disagree with Saudi universities closing their SEBP, while 35% support it as a positive step toward updating curricula and addressing teacher competency issues. The results of the study can support decision-makers in improving SEBP based on the needs of the labor market and society and enhancing educational and rehabilitation programs to support PWD in KSA. The study recommended proposals for integrating special education programs in Saudi universities, reopening the Bachelor of Education program, adapting curricula, offering master's and doctoral programs, and focusing on early childhood to primary school specializations, such as those offered by international universities.